PEMBUATAN WEBSITE PROFIL SEKOLAH DASAR NEGERI 03 KALISORO - Pringgo Winoto -Program Studi Teknik Informatika, Universitas Surakarta; PEMBUATAN WEBSITE PROFIL SEKOLAH DASAR N -Program Studi Teknik Informatika, Universitas Surakarta (APMMI - Asosiasi Profesi Multimedia Indonwsia, 2017)
ABSTRACT: Today many people are familiar with even use the internet in everyday life, so that in thesearch for community information is also often take advantage of the Internet media. KalisoroElementary School 03do not have the media to deliver information quickly and accurately, so far indelivery of information is still using banner of course this will take a lot of time and cost. This is one ofthe obstacles to improving the quality of education in public elementary school 03 Kalisoro .In this research, the website will be made regarding the profiles of public elementary school 03Kalisoro, to promote elementary school 03 Kalisoro with an attractive appearance and can beaccessed easily from anywhere via the Internet. That way elementary school 03 Kalisoro will be moreknown and unknown by the general public to view the profiles that are online.The method performed in the study include: literature, observation, analysis and design, websitecreation, implementation. Elementary School District 03 Kalisoro already have a website, so thatpeople can find information about the 03 State Primary Schools Kalisoro online.This website is therange of information provided not only the wider community but from all corners capable of knowingElementary School 03 Kalisoro with more complete and clear through the internet.Keywords : Website Profil